Pengaruh Citra Merek, Kualitas Produk, Sertifikat Halal Dan Keputusan Pembelian Terhadap Permintaan Produk Hand Body Lotion Citra (Studi Kasus : Pada Masyarakat Kelurahan Dwikora, Kecamatan Medan Helvetia) - Aprillia, Wina; Harmain, Hendra; Jannah, Nurul (Universitas Labuhanbatu, 2023)
This study aims to determine the effect of brand image, product quality, halal certificates, and purchasing decisions on product demand. This research was conducted using a quantitative approach. The population in this study amounted to 300 with a sample of 75. The sampling method was simple random sampling technique. This study uses primary data using multiple linear regression data analysis using SPSS 15. Based on the results of the first hypothesis test, it is known that the significant value of brand image is 0.085 (sig > 0.05) with a t-count value of 1.750 <1.994 (t-count < t-table). The second hypothesis test showed a significant product quality of 0.825 (sig > 0.05) with a t-count value of 0.222 <1.994 (t-count < t-table), the third hypothesis test showed a significant halal certificate of 0.486 (sig > 0.05) with a t-count -0.700 < 1.994 (t-count < t-table), the fourth hypothesis test showed a significant 0.000 (sig < 0.05) with a t-count value of 4.368 > 1.994 (t-count > t-table). Based on the results of the fifth hypothesis test, it is known that the significant value is 0.000 (sig <0.05) with an f-count value of 22.193 > f-table 2.503. The results of this study indicate that Brand Image, Product Quality, Halal Certificate and Purchasing Decision simultaneously influence product demand.